Analysis of the Performance of State Civil Apparatus in Public Services in the Office Dungingi Sub-district Head, Gorontalo City - Hindun A. Djafar; Srihandayani Suprapto; Dian Fitriani Karim; Salma Rivani Luawo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Public services are an important indicator in assessing the performance of the government, especially the State Civil Apparatus (ASN) as the main implementer of services to the community. However, in practice, the performance of civil servants still faces various obstacles such as lack of understanding of main tasks and functions, low use of information technology, and suboptimal time discipline, so that it has an impact on the effectiveness of public services. This study aims to analyze the performance of civil servants in public services at the Dungingi Sub-district Office, Gorontalo City and identify the factors that affect it. This study uses a qualitative approach with a descriptive type of research. The results of the study show that the performance of civil servants is not fully optimal. Based on four indicators, namely ability, initiative, punctuality, and quality of work results, it was found that three indicators of ability, initiative, and punctuality still face obstacles. Meanwhile, the quality of work results is the best indicator, with service results that are relatively accurate, neat, and according to the needs of the community. In conclusion, improving the performance of civil servants needs to be focused on strengthening capabilities, increasing initiatives, and improving discipline and the use of technology so that public services can run more effectively, efficiently, and of high quality.